Effects of liquid fuels and alcohols on the pollutant emissions of a spark ignition engine - Gonca, Guven; Genc, Ibrahim (INDERSCIENCE ENTERPRISES LTD, 2021)
The presented work investigates the impacts of various liquid fuels and alcohols including methanol, ethanol, toluene, hexane, benzene, isooctane and gasoline on a spark ignition (SI) engine's performance and combustion products. A verified mathematical model with empirical data has been utilised to indicate the various fuel type impacts on the emission outputs and combustion specifications of a SI engine. An artificial neural network (ANN) model for the system is also presented to show that the system can be approximated more densely compared to numeric methods with the advantage of less computational complexity.
Keywords: alcohols; combustion; liquid fuels; pollutant emissions; spark ignition engine; artificial neural networks; ANNs; STEAM INJECTION; DIESEL-ENGINE; PERFORMANCE-CHARACTERISTICS; SYSTEM; Environmental Sciences & Ecology